Ferroptosis: Is it both cause and effect in refractory epilepsy? - Auzmendi, Jerónimo Andrés (2025)
All living beings, from microorganisms to plants, animals, and humans, require iron as an essential micronutrient for their lives. However, iron overload can constitute a scenario prone to damage to the organism, including oxidative stress, deterioration of cellular and subcellular membranes, and thus leading to cell death. This process involves unrestricted lipid peroxidation caused by the generation of reactive oxygen species (ROS) because of an abrupt increase in free Fe2+ in the cytoplasm, all of which leads to subsequent membrane damage and iron-dependent cell death, now known as “ferroptosis”. This process can be induced by convulsive stress, and conversely, inducing seizures, and in both situations under a context of neuroinflammation. In this critical review, we will highlight the most relevant aspects of this recently described mechanism, which has been studied little in epilepsy, its impact on the prognosis of the disease, and its effects on the development of central and/or peripheral comorbidities, including SUDEP (sudden unexpected death in epilepsy).